PENGARUH MANAJEMEN LABA TERHADAP BIAYA MODAL PADA PERUSAHAAN GO PUBLIK SEKTOR JASA YANG TERDAFTAR DI BURSA EFEK INDONESIA - ARIEF FATHURAHMAN; YANA ULFAH; IRWANSYAH - (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2016)
The purpose of this research is to find empirical evidence of earnings management influence on the cost of capital. This research was based accounting capital market as it aims to determine the effect of earnings management to investment decisions by investors. The population in this study is the service sector companies listed on the Indonesia Stock Exchange during the period 2010-2013. Samples were selected based on purposive sampling method or technique of making certain criteria. Earnings management is measured by the ratio of working capital to sales accruals and capital costs estimated by the model Ohlson. The hypothesis was tested using multiple linear regression analysis. Based on test results, it was found that the effect is strong earnings management or effect on the cost of capital. This shows that investors have been anticipating precisely on accrual information to determine earnings management practices.Keywords: Earnings Management, Cost of Capital.